2016
DOI: 10.3390/antiox5040037
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Dietary Berries in Cancer

Abstract: Dietary patterns, including regular consumption of particular foods such as berries as well as bioactive compounds, may confer specific molecular and cellular protection in addition to the overall epidemiologically observed benefits of plant food consumption (lower rates of obesity and chronic disease risk), further enhancing health. Mounting evidence reports a variety of health benefits of berry fruits that are usually attributed to their non-nutritive bioactive compounds, mainly phenolic substances such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 93 publications
0
53
0
3
Order By: Relevance
“…Besides vitamin C, other natural compounds also have bioactivities like polyphenols, flavonoids, anthocyanins and resveratrol, etc. (8,9). With the increasing focus on plant-derived polyphenols, anthocyanins have been brought into the wide concern because of their potential benefits for human health (10).…”
mentioning
confidence: 99%
“…Besides vitamin C, other natural compounds also have bioactivities like polyphenols, flavonoids, anthocyanins and resveratrol, etc. (8,9). With the increasing focus on plant-derived polyphenols, anthocyanins have been brought into the wide concern because of their potential benefits for human health (10).…”
mentioning
confidence: 99%
“…As the result of inflammation, different types of immune cells are in the process of either tumor promoting mechanisms or anti-tumorigenic mechanisms by producing the reactive oxygen species, reactive nitrogen intermediates, cytokines, and chemokines in tumor initiation and promotion [46,47]. Among the dietary factors, numerous studies have reported that phytochemicals such as flavonoids rich in fruits and vegetables mainly contributed to regulation of immune system via production of antioxidants and scavenging activity [48][49][50]. Previous epidemiological studies have reported the associations between dietary antioxidants and cancer suggesting the role of the inflammation [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other phytochemicals, berries also possess antioxidant, anticancer, neuroprotective, and antiinflammatory effects (Joseph, Edirisinghe, & Burton-Freeman, 2014). Antiangiogenic and proapoptotic role of berries has also been demonstrated in vitro (George & Abrahamse, 2019;Kristo et al, 2016;Seeram et al, 2006). Berry extract has been shown to inhibit the growth of human colon (HT-29, HCT116), prostate carcinoma (LNCaP), breast cancer (MCF-7), and oral cancer (KB and CAL27) cells.…”
Section: Berrymentioning
confidence: 98%
“…Berries are widely consumed in our diet and have sought attention due to their potential benefits on human health (Miller, Feucht, & Schmid, ; Pan et al, ). Berries are being investigated for their potential chemopreventive effects as well as a protective role against various types of chronic diseases (Kristo, Klimis‐Zacas, & Sikalidis, ; Stoner, ). Berries may have different constituent phenolic compound such as anthocyanins, flavanols, flavonols, ellagitannins, proanthocyanidins, and phenolic acids (Seeram, ; Afrin et al, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%